Cyclic Loading of a Notched Element with a Technological Surface Layer - Kucharski, S. (Engineering Transactions, 1995)
A method for determining the stresses in a notched element with a technological surface layer (TSL) subjected to low-cycle loading is presented. The considerations are based on the kinematic-isotropic model of strain hardening and the theory of plastic flow. The hysteresis loops obtained for a specimen with and without a surface layer, under the same loading conditions are compared with each other. The same is done for the working and residual stresses for a specimen with a surface layer.